APOL1 Risk Alleles Are Associated With More Severe Arteriosclerosis in Renal Resistance Vessels With Aging and Hypertension - Michael D. Hughson; Wendy E. Hoy; Susan A. Mott; Victor G. Puelles; John F. Bertram; Cheryl A. Winkler; Jeffrey B. Kopp (Kidney International Reports, 2016)
The increased risk of end-stage kidney disease among hypertensive African Americans is partly related to APOL1 allele variants. The initial glomerulosclerosis of hypertension-associated arterionephrosclerosis consists of focal global glomerulosclerosis, but in biopsy studies, focal segmental glomerulosclerosis is found with progression to end-stage kidney disease, particularly in African Americans. Methods: This is a study of arterionephrosclerosis in successfully APOL1-genotyped autopsy kidney tissue of 159 African Americans and 135 whites aged 18 to 89 years from a general population with no clinical renal disease. Results: Glomerulosclerosis was nearly exclusively focal global glomerulosclerosis with 3 subjects having focal segmental glomerulosclerosis–like lesions that were unrelated to APOL1 risk status. For both races, in multivariable analysis, the dependent variables of arteriosclerosis and glomerulosclerosis were significantly related to the independent variables of older age (P < 0.001) and hypertension (P < 0.001). A relationship between APOL1 genotype and arteriosclerosis was apparent only after 35 years of age, when, for any level of elevated blood pressure, more severe arteriosclerosis was found in the interlobular arteries of 14 subjects with 2 APOL1 risk alleles compared to African Americans with none (n = 37, P = 0.02) or 1 risk allele (n = 35, P = 0.02). Discussion: With the limitation of the small number of subjects contributing to the positive results, the findings imply that APOL1 risk alleles recessively augment small-vessel arteriosclerosis in conjunction with age and hypertension. Focal segmental glomerulosclerosis was not a significant finding, indicating that in the early stages of arterionephrosclerosis, the primary pathologic influence of APOL1 genotype is vascular rather than glomerular.